Mutual exclusivity and phonological novelty constrain word learning at 16 months. - Mather, E; Plunkett, K (2011)
Studies report that infants as young as 1 ; 3 to 1 ; 5 will seek out a novel object in response to hearing a novel label (e.g. Halberda, 2003; Markman, Wasow and Hansen, 2003). This behaviour is commonly known as the 'mutual exclusivity' response (Markman, 1989; 1990). However, evidence for mutual exclusivity does not imply that the infant has associated a novel label with a novel object. We used an intermodal preferential looking task to investigate whether infants aged 1 ; 4 could use mutual exclusivity to guide their association of novel labels with novel objects. The results show that infants can successfully map a novel label onto a novel object, provided that the novel label has no familiar phonological neighbours. Therefore, as early as 1 ; 4, infants can use mutual exclusivity to form novel word-object associations, although this process is constrained by the phonological novelty of a label.